Análisis evolutivo y diferenciativo de la percepción rorschach a través de los factores de localización - Jiménez Gómez, Fernando (1991)
This study deals with the analysis of the evolution of different personality factors through the aperceptive engrams of the Rorschach Psychodiagnostic Test, in two different age groups of adolescents and adults, eleven to sixty years age, in a sample of Spanish subjetcs from the broad and varied peninsular geography. The sample is 526 adolescents and 300 adults, 424 males, 402 females. The mean age of adolescents is 15 years, 6 mo. and of adults, 37 years. Frorn the differents aspects of the Rorschach Psychodiagnostic Test, we focused attention on the typical factors of Localization.